Pengaruh Sistem Informasi Akuntansi Manajemen, Human Capital, dan Ketidakpastian Lingkungan terhadap Kinerja Manajerial pada Badan Amil Zakat Nasional Provinsi Jambi - M. Andrey Al Thariq; Mellya Embun Baining (ARZUSIN, 2025)
The Badan Amil Zakat Nasional (BAZNAS), as a non-structural government institution, holds a strategic responsibility in the national management of zakat, requiring a professional, accountable, and adaptive management system in response to environmental dynamics. However, the effectiveness of zakat institution management often faces challenges, particularly in optimizing information systems, human resource quality, and coping with external uncertainties. This study aims to analyze the influence of Management Accounting Information Systems (MAIS), Human Capital (HC), and Environmental Uncertainty (EU) on managerial performance at BAZNAS of Jambi Province. A quantitative approach was employed using a survey method involving employees and managers as respondents. The questionnaire instrument was tested for validity and reliability, and the data were analyzed using multiple linear regression to assess both partial and simultaneous effects among variables. The results show that both MAIS and HC have a positive and significant influence on managerial performance, while EU does not have a significant effect. Simultaneously, the three variables have a significant influence on managerial performance. These findings emphasize the importance of effective MAIS implementation and human resource capacity building in enhancing the managerial performance of zakat institutions and strengthening organizational governance based on sharia principles.